“Aušros” žanrai - Bulota, Jonas (Knygotyra, 1995)
Though “Aušra” was not the first Lithuanian periodical, the researchers are inclined to link it with the appearance of professional Lithuanian journalism. In 1883–1886 mostly because of political situation “Aušra” was an issue of syncretic character. Therefore in the beginning of the article we discuss the origin of the terms “newspaper” and “magazine” in Lithuanian periodical press, the introduction of the neologism “laikraštis” instead of the loanwords “gazieta”, “ceitunga” and others, used before. The authorship of the neologism, at the beginning applied both to newspapers and magazines, is ascribed with some reservation to Jonas Basanavičius. The main part of the article reveals objective and subjective reasons, that influenced the genres of the periodical, issued and edited outside Lithuania and spread illegaly. The genres were selected spontaneously according to the wishes and skills of the authors, not planed by the editorship. Mostly it was all kinds of articles. A lot of place was given to critique and history. Original literary works were presented mostly by verse and translations of poetry. We can find the main information genres or at least their plot (rudiments) in the regular chapter “From Lithuania”, resembling a newspaper very often. Those genres are: news items, information, report, correspondence. There were also some rudiments of scenes, pamphlet, feuilleton. The mastership of this publication depended a great deal on the intelligence, experience and inborn talent for journalism of the contributors. The experience, obtained by the editors and collaborators of the magazine, issued not long, had a great influence on the further history of Lithuanian periodical press.